2013
DOI: 10.1590/s0366-69132013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-gallium oxynitride powders: effect of the oxide precursor synthesis route

Abstract: Zinc-gallium oxynitride powders (ZnGaON) were synthesized by nitridation of ZnGa 2 O 4 oxide precursor obtained by polymeric precursors (PP) and solid state reaction (SSR) methods and the influence of the synthesis route of ZnGa 2 O 4 on the final compound ZnGaON was investigated. Crystalline single phase ZnGa 2 O 4 was obtained at 1100 o C / 12 h by SSR and at 600 o C / 2 h by PP with different grain sizes and specific surface areas according to the synthesis route. After nitridation, ZnGaON oxynitrides with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(61 reference statements)
2
8
0
Order By: Relevance
“…Gallium compounds12345 including gallium nitride (GaN), gallium oxide (Ga 2 O 3 ) and more recently gallium oxynitrides (GaON/Ga 3 O 3 N/Ga x O y N z ) have been known for their semiconducting and optoelectronic properties6789. These gallium materials in different morphologies have enlightened ample of applications e.g.…”
mentioning
confidence: 99%
“…Gallium compounds12345 including gallium nitride (GaN), gallium oxide (Ga 2 O 3 ) and more recently gallium oxynitrides (GaON/Ga 3 O 3 N/Ga x O y N z ) have been known for their semiconducting and optoelectronic properties6789. These gallium materials in different morphologies have enlightened ample of applications e.g.…”
mentioning
confidence: 99%
“…Figueredo et al reported on the significant change of morphology after the nitridation process of ZnGa2O4 precursor using NH3 gas [11]. For our 2D ZnGa2O4 precursor, it is postulated that the micrometer scale plate-like oxides coarsened to generate such a 3D cauliflower-like morphology as a result of the conversion of crystal structures from spinel phase of ZnGa2O4 to wurtzite phase of (Ga1-xZnx)(N1-xOx) [1], although the detailed mechanism is not clear at present.…”
Section: Formationof Zinc Gallium Oxynitride (Ga1-xznx)(n1-xox)mentioning
confidence: 75%
“…This result suggested that the nitridation of single-phase ZnGa2O4 does not produce an oxynitride compound [2]. The loss of zinc may cause a reduction of ZnO to metallic Zn during the nitridation [1,11,16,17], suggesting that the presence of zinc oxide is required to efficiently synthsize (Ga1-xZnx)(N1-xOx). Therefore, ZnO-rich ZG2-1 and ZG1-1 samples were used for the nitridation.…”
Section: Formationof Zinc Gallium Oxynitride (Ga1-xznx)(n1-xox)mentioning
confidence: 99%
See 2 more Smart Citations